Histone H3K9 Acetyltransferase PCAF Is Essential for Osteogenic Differentiation Through Bone Morphogenetic Protein Signaling and May Be Involved in Osteoporosis. (27th June 2016) - Zhang, Ping; Liu, Yunsong; Jin, Chanyuan; Zhang, Min; Lv, Longwei; Zhang, Xiao; Liu, Hao; Zhou, Yongsheng
Abstract: Human mesenchymal stem cells (MSCs) are multipotent progenitor cells that can differentiate into osteoblasts, chondrocytes, and adipocytes. The importance of epigenetic regulation for osteogenic differentiation of MSCs is widely accepted. However, the molecular mechanisms are poorly understood. Here, we show that histone H3K9 acetyltransferase PCAF plays a critical role in osteogenic differentiation of MSCs. Knockdown of PCAF significantly reduced the bone formation both in vitro and in vivo. Mechanistically, PCAF controls BMP signaling genes expression by increasing H3K9 acetylation. Most importantly, PCAF expression is significantly decreased in bone sections of ovariectomized or aged mice. Histone modification enzyme is chemically modifiable; therefore, PCAF may represent a novel therapeutic target for stem cell-mediated regenerative medicine and the treatment of osteoporosis. Abstract : Osteogenic differentiation induced PCAF expression through SMADs; PCAF promoted activation of BMP2, BMP4, BMPR1B and RUNX2 by increasing H3K9ac, which led to osteogenic differentiation.